TINDAK UJAR KONFLIKTIF DALAM FILM THE KINGDOM OF HEAVEN KARYA WILLIAM MONAHAN - RONDONUWU, CHRISTAMI PRETTY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTSLanguage is one of the characteristics of human beings that differentiate them from other creatures. In this case, human beings use language as a tool of communication. In uttering something, people are not only sounding sentence, but also transferring it into behavior. This is called speech acts illocutionary act is one of the aspects of it. This study focuses on one of the categories of illocutionary act, conflictive act that is used in the film The Kingdom of Heaven by William Monahan.In collecting data, the writer elicits them through the conversation among the characters in the film. To analyze them, the writer used descriptive analysis based on Leechâ€™s theory. Leech divided conflictive act into four kind which is threatening, reprimanding, accusing, and cursing.Â It is excpected that the study will help student and readers in learing pragmatics especially the conflictive act in the film. It is suggested for researchers to use another theory of illocutionary acts in other objects such as native language, novel, short story and many others.__________Keywords : speech act; illocutionary act; conflictive act